Association of Dairy Foods in Acne Vulgaris (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: Acne vulgaris is one of the most commonly found skin problems affecting teenagers and adolescents. Dietary foods particularly dairy products consist of milk or any of its food made from milk are frequently regarded by patients and clinicians as a cause or aggravator of acne. As there are very limited studies found on this regard, this study was aimed to find the association of dairy foods in acne vulgaris.Methods: This wasa cross-sectional analytical study and was carried out in the Dermatology and Venereology department of Shaheed Suhrawardy Medical College Hospital. Total 260 patients were selected by appropriate inclusion criteria equally into two groups: Group A (diagnosed with acne vulgaris, n=130) and group B (patients not having acne vulgaris, n=130). A thorough history of every patient and face to face interview was taken by a predesigned questionnaire after getting the written informed consent of the patient. Data were collected in predetermined data collection form. Result were subjected to standard statistical evaluation and were analyzed by SPSS-24.Results: According to the age group, majority of the acne patients were between 10-20 years (75.4% in group A and 63.8% in group B, p